Seismic Design and Performances of Frame Structures Connected to a Strongback System and Equipped with Different Configurations of Supplemental Viscous Dampers - Palermo, Michele; Laghi, Vittoria; Gasparini, Giada; Silvestri, Stefano; Trombetti, Tomaso (Frontiers in Built Environment, 2021)
The paper investigates the dynamic behavior of structural systems obtained by connecting a moment resisting frame structure with a vertical rigid truss pinned at the base, known in literature as “strongback”, and equipped with added fluid-viscous dampers. The strongback, designed in order to remain in the elastic field under strong seismic ground motion, acts as a mast by imposing to the structure a linear lateral deformed shape. By regularizing the lateral drift profile of the structure, the strongback limits undesired effects such as weak-storey mechanisms, damage concentration and residual drifts. In addition, when supplemental dampers are inserted in the structure, a considerable amount of energy can be dissipated, thus reducing the peak seismic response. The aim of the work is twofold: (i) to provide analytical formulations for the preliminary design of added dampers based on the Generalized Single Degree of Freedom (GSDOF) concept, and (ii) to evaluate the increase in energy dissipation capabilities for selected dampers configurations thanks to the presence of the strongback. The formulas are developed for different configurations of added viscous dampers: dampers inserted within the frame between consecutive storeys (inter-storey placement) and dampers located at the base of the strongback to realize a rigid “dissipative tower”. The effectiveness of the dampers configurations is evaluated through dynamic analyses.